K-MEANS CLUSTERING CALCULATION TO DETERMINE MAINSTREAM DOMINATION OF COURSES - Anggraeni, Dewi; Rizaldi, Rizaldi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2023)
Abstract : In Semester 6 students are required to choose mainstream elective courses at the STMIK Royal campus. In this study, researchers chose 2 mainstraim elective courses, namely Logic and Programming, and Database and Information Management. The purpose of choosing this elective course is for students to focus more on their majors. The process of selecting the data, researchers carry out an analysis process of student learning outcomes. This research data is semester 1 to semester 5 grades. All data on the value of student learning outcomes are divided into 2 parts, namely theory and practice and divided into the number of courses. For many uses, a data mining method using K-means cluster is needed. K-Means Clustering is a data analysis method or Data Mining method that performs an unsupervised learning modeling process and uses methods that group data from various partitions. The results of the k means clutering grouping with 2 clusters, namely cluster 0 of the mainstream group of logic and programming courses with a total of 28 students, and cluster 1 of the mainstream group of informatics database and management courses with a total of 72 students with a total of 100 students. Keywords: data; K-means; student Abstrak : Mahasiswa semester 6 diwajibkan memilih mainstream matakuliah pilihan yang ada di kampus STMIK Royal. Pada penelitian ini, peneliti memilih 2 mainstraim matakuliah pilihan yaitu Logika dan Pemprograman, serta Basis Data dan Manajemen Informatika. Tujuan pemilihan matakuliah pilihan ini adalah agar mahasiswa lebih terfokus pada jurusannya. Proses pemilihan datanya, peneliti melakukan proses analisa dari hasil belajar mahasiswa. Data penelitian ini nilai semester 1 sampai semester 5. Seluruh data nilai hasil belajar mahasiswa dibagi menjadi 2 bagian yaitu teori dan praktek serta dibagi jumlah banyaknya matakuliah. untuk penggunaan yang banyak, maka dperlukan metode data mining dengan menggunakan k-means cluster. K-Means Clustering adalah metode analisis data atau metode Data Mining yang melakukan proses pemodelan pembelajaran tanpa pengawasan dan menggunakan metode yang mengelompokkan data dari berbagai partisi. Hasil pengelompokan k means clutering dengan 2 cluster yaitu cluster 0 kelompok mainstream matakuliah logika dan pemprograman dengan jumlah mahasiswa 28 orang, dan cluster 1 kelompok mainstream matakuliah basis data dan manajemen informatika dengan jumlah mahasiswa 72 orang dengan total keseluruhan 100 mahasiswa. Keyword : data; K-means; mahasiswa;